노인장기요양보험 재가급여 이용 노인의 약물사용실태 및 약물오용 영향요인 - 이보경; 부선주; Lee, Bogyeong; Boo, Sunjoo (Chunghwanja Kanho Hakhoe chi, 2025)
Purpose : This study examined the status of medication use and factors associated with medication misuse among older adults receiving in-home services under Long-Term Care Insurance. Methods : A cross-sectional survey was conducted among 134 older adults aged 65 years and above who had registered at nine daycare centers. Data were collected through structured interviews regarding sociodemographic characteristics, depression, activities of daily living, cognitive function, social support, and medication misuse. Descriptive statistics and logistic regression were used for analysis. Results : On average, they were administered medications 1.98 times daily and consumed 4.41 medications per administration. Medication misuse was observed in 28.4% of the participants. Factors significantly associated with medication misuse included depression, lower monthly household income (OR=3.34, 95% CI: 1.30-8.56), and the experience of medication side effects (OR=9.67, 95% CI: 2.05-45.64). Conclusion : The findings of this study highlight the need for integrated interventions that include regular screening for depression and the close monitoring of medication-related adverse events. Enhancing the involvement of daycare center staff-particularly nursing personnel-in medication education and supervision is advised to mitigate misuse and promote safe medication practices.